Stability Analysis and Almost Periodic Solutions for Quaternion-Valued Cellular Neural Networks with Leakage Term on Time Scales - Khuddush, Mahammad; Prasad, K. Rajendra (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we consider a quaternion-valued cellular neural networks with time varying delays in leakage term on time scales. We derive sufficient conditions for the existence, uniqueness and global exponential stability of almost periodic solutions by using contraction mapping principle and exponential dichotomy of linear dynamic equations. Finally, a numerical example is provided to illustrate the feasibility of our results.